A174 TYPE OF DIETARY FAT INFLUENCES DISEASE ACTIVITY IN A MURINE MODEL OF CHRONIC INTESTINAL INFLAMMATION. (15th March 2019) - Haskey, N; Ye, J; Barnett, J; Callaway, A; Ghosh, S; Gibson, D L
Abstract: Background: There is growing appreciation that the interaction between diet, the gut microbiota and the immune system contribute to the development and progression of colitis. The current hypothesis suggests an inappropriate and chronic activation of the immune system due to an abnormal intolerance to the gut microbiota. While dietary factors affect the functionality of intestinal epithelial cells and the underlying immune cells, dietary antigens alter the intestinal ecosystem enabling certain microbial populations to proliferate and dampen the dominance of others. High fat diets have been shown to result in dysbiosis, however our lab has clarified that the type of fat, not total calories derived from fat, influence gut dysbiosis and immunity. The n-6 polyunsaturated fatty acids (PUFA) promote colitis, monounsaturated fatty acids (MUFA) protect against colitis. The benefits of n-3 PUFA appear to be dependent on the presence of saturated fat (SFA) being present in the diet. Based on these results, we hypothesize that a blend of fats, similar the Mediterranean Diet Pattern (MDP) could be beneficial to colitis. Aims: To clarify the effects of different types of dietary fat in colitis by studying dietary fats in isolation from each other, as well as in combination similar to the MDP. Methods: Mucin2-deficient mice were weaned at day 21 on to isocaloric, isonitrogenous rodent chow blended with 20% w/w of either olive oil, anhydrous milk fat (AMF), corn oil or MDP for 9 weeks (n=10–12 male and females/group). Food intake, water intake and disease activity scores were measured weekly. Disease activity was determined by assessing general appearance, weight, blood in the stool, stool consistency and rate of rectal prolapse. Glucose tolerance testing was performed at week 9 of the diet intervention. Results: Body weight, energy and fluid intake were similar between groups. Mice fed corn oil and AMF had significantly higher disease activity scores than MDP and olive oil (p<0.05), with more diarrhea, increased rectal swelling and blood found in the stool. Males fed corn oil (n=2) and AMF (n=1) developed spontaneous rectal prolapse (clinical endpoint). The corn oil resulted in impaired glucose tolerance compared to the AMF or MDP (p<0.0001). Statistically significant sex differences (p<0.05) were also found based on the type of fat consumed. Conclusions: The type of fat consumed, not total calories from fat, resulted in differing responses to disease activity, rates of rectal prolapse and glucose tolerance, which were also sex-dependant. We confirm that fats derived from n-6 PUFA are detrimental to colitis and a diet rich in MUFA is protective. Partial protection provided by the MDP and olive oil diets may be through alterations in the gut microbiome and its immune effects. Further work will confirm these hypotheses. Funding Agencies: CAG, CCC, CIHR